Construction and validation of a Standard Operational Procedure for venipuncture with instructional therapeutic toy (Research, Society and Development, 2023)
Objective: to build and validate a Standard Operating Procedure (SOP) for preparing children for venipuncture using an Instructional Therapeutic Toy (ITTB). Methodology: applied research, methodological, of quantitative approach, developed in 3 phases: 1) integrative literature review in databases, 2) construction of the Standard Operating Procedure; 3) validation of content and appearance by expert nurses. Results: from the integrative review, 8 items with 42 sub-items composed the initial instrument. The 8 items are: initial instructions, protocol composition, necessary materials, description of steps, material handling, expected results, actions in case of non-compliance, references. The content validation occurred through the analysis of the agreement rate of the items and sub-items by calculating the Content Validity Index (CVI). The Standard Operating Procedure, evaluated for its clarity and relevance, obtained a Content Validation Index of 0.97 and the exclusion of some items by the experts. The final version of the SOP was composed of 8 items and 38 sub-items. Conclusion: a content-validated instrument was obtained for pediatric nurses to be implemented and applied in the hospital environment, in order to contribute to a more humanized and safe care of children. As a limitation of the study, we highlight the small number of studies that use the BTI approach in pediatrics, in both tertiary and primary care. The study points to the need for other investigations of a similar nature, especially regarding its applicability by professionals, patients and families.